Penerapan Desain Pembelajaran Tematik Integratif Alternatif Berbasis Kearifan Lokal untuk Meningkatkan Hasil dan Kebermaknaan Belajar - Khoeriyah, Ni'matul; Mawardi, Mawardi (Mimbar Sekolah Dasar, 2018)
This research aims to improve the outcomes and meaningfulness of learning by applying alternative integrative thematic design based on local wisdom. This study is a class action research on the Stringer model which carried out in two cycles. Data collection instruments used were question instruments, observation sheets, questionnaires, and documentation. Data analysis was done by a comparative description. The result of the research showed an increase in outcomes and the significance of meaningful learning. It was supported by the thoroughness of thematic learning outcomes in Indonesian language, IPS, and PPKn respectively in the 1st cycle 72,5%, 52,5%, and 65%. The result of the 2nd cycle was 90%, 75%, and 77,5%. Furthermore, the significant increase of learning meaningfulness in categories is shown in 1st cycle which was 87.5% and increased to 95% in 2nd cycle. To conclude, the outcomes and learning meaningfulness of 4th grade SDN Gendongan 02 are improved by alternative integrative thematic learning based on local wisdom.